Answer
x = 3 ± i
x = (3 + i)
OR
x = (3 - i)
Step-by-step explanation
To solve this, we need to note that √(-1) = i
So, for this simplification
√(36 - 40) = √(-4) = √[(4)(-1)] = 2i
We can now fully simplify the expression given
![\begin{gathered} x=\frac{6\pm\sqrt[]{36-40}}{2} \\ =(6\pm2i)/(2) \\ =(6)/(2)\pm(2i)/(2) \\ =3\pm i \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/dxvbdq7zayrnd3jxgbhs17o0bqr8binq60.png)
x = 3 ± i
x = (3 + i)
OR
x = (3 - i)
Hope this Helps!!!